Surgical Management of Pancreatitis in Children: An Observational Study - Shamsuddin, A K M; Rahman, Md Mamunur; Sarwar, Jahangir Md; Rahman, Md Atiar; Banik, Sanjit Kumar (Community Based Medical Journal, 2025)
Pancreatitis in children is uncommon. Treatment is usually supportive and non-surgical. However, surgery may be needed for complications like infected necrosis or pseudocysts and dilated main pancreatic duct with calculi. The timing of surgery is critical. Understanding surgical indications helps optimize treatment. This observational study aims to establish evidence-based guidelines by assessing surgical techniques and outcomes in children, which was conducted in the Department of Paediatric Gastro-surgery, National Gastroliver Institute & Hospital, Dhaka, Bangladesh, between February 2022 and February 2024. A total of 24 children who underwent pancreatic surgery were enrolled using a purposive sampling technique. Data collected included demographic information, clinical details, surgical outcomes, and complications. At the one-year follow-up, 62.5% of cases achieved full recovery, and 25% recovered from the initial episode. Residual problems without recurrence occurred in 8.3% of cases, with a 4.2% mortality rate. Postoperative complications included pancreatic necrosis and pseudocyst formation in 12.5% of patients, respiratory failure and hyperglycemia in 8.3%, and circulatory collapse, renal failure, gastrointestinal bleeding, and diabetes each in 4.2% of patients. Surgical management of pancreatitis in children showed a good recovery rate, but recurrence was a challenge. CBMJ 2025 July: vol. 14 no. 02 P:4-8